Weber Revisited: The Protestant Ethic and the Spirit of Nationalism - Felix Kersting; Iris Wohnsiedler; Nikolaus Wolf (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We revisit Max Weber's hypothesis on the role of Protestantism for economic development. We show that nationalism is crucial to both, the interpretation of Weber's Protestant Ethic and empirical tests thereof. For late nineteenth-century Prussia we reject Weber's suggestion that Protestantism mattered due to an “ascetic compulsion to save”. Moreover, we find that income levels, savings, and literacy rates differed be-tween Germans and Poles, not between Protestants and Catholics, using pooled OLS and IV regressions. We suggest that this result is due to anti-Polish discrimination.
Keywords: N13; N33; O16; Z12; 330; Max Weber; protestantism; nationalism